Efficient syntheses of streptocarpone and (±)-α-dunnione - Pérez Sánchez, Alice Lorena (2007)
An efficient divergent synthesis of both streptocarpone and racemic α-dunnione from lawsone are described. A one-pot, formal [3+2] cyclization to form a furanonaphthoquinone directly provided a common intermediate.